Lightweight closed-cell macrobeads for solid buoyancy material, and method of making and use thereof
Patent Information
- Application Number
- CN202611287511.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-09
AI Technical Summary
该技术虽然一定程度上降低了成本,但存在以下本质缺陷:第一,核壳界面问题:EPS内核与环氧树脂外壳之间为物理结合,无化学键合,在高压环境下容易发生核壳脱层,导致浮力损失;第二,工艺效率低:需要反复涂覆-固化数十次,生产周期长达数小时,产品一致性差;第三,比强度低:外壳厚度0.5~2.5mm,且含有大量纤维,外壳密度高;第四,尺寸受限:常规量产直径多在50mm以内
[0031](1)反应控制创新,分步有序交联:本发明采用高活性端伯羟基聚醚多元醇(伯羟基含量≥80%),利用伯羟基与小分子扩链剂的反应活性差异,实现“先成骨架、后交联”的分步反应。交联网络均匀致密,泡孔结构均一,孔径变异系数≤15%,有效解决了传统聚氨酯发泡交联不均、内应力大的问题。
Smart Images

Figure CN122878739A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer composite materials technology, specifically relating to a lightweight closed-cell bead for solid buoyancy materials, its preparation method and application, and is particularly suitable for the lightweight filling phase of high-strength, low-density solid buoyancy materials for deep-sea exploration at depths of 1000-2000 meters and marine oil and gas development. Background Technology
[0002] Solid buoyancy materials are core foundational materials for deep-sea engineering equipment, and their performance directly determines the effective load capacity and safety reliability of underwater operating systems. Currently, commercially available solid buoyancy materials mainly use epoxy resin as the matrix, filled with hollow glass microspheres to prepare composite foam materials. However, hollow glass microspheres have inherent defects such as high cost (accounting for more than 60% of the raw material cost), easy breakage during the mixing process, a maximum particle size of no more than 200μm, and poor interfacial bonding with the resin matrix, which seriously restrict the large-scale application and performance improvement of solid buoyancy materials.
[0003] To address the aforementioned issues, the industry has conducted research on polymer hollow spheres as a substitute for hollow glass microspheres. Chinese patent CN105037789A discloses a fiber-reinforced resin composite hollow sphere, which uses steam-foamed polystyrene (EPS) microspheres as its core. Multiple layers of fiber-reinforced epoxy resin are coated onto the EPS surface through a repeated coating process in a roller to prepare hollow spheres with a diameter of 250mm. While this technology reduces costs to some extent, it suffers from the following inherent drawbacks: First, the core-shell interface problem: the EPS core and epoxy resin shell are physically bonded without chemical bonding, making them prone to delamination under high pressure, leading to buoyancy loss; Second, low process efficiency: it requires dozens of coating-curing cycles, resulting in a production cycle of several hours and poor product consistency; Third, low specific strength: the shell thickness is 0.5~2.5mm, and it contains a large amount of fiber, resulting in a high shell density; Fourth, size limitations: conventional mass-produced diameters are mostly within 50mm.
[0004] Chinese patent CN1827691A discloses a buoyancy material with a microsphere / cell composite structure, comprising hollow microspheres uniformly distributed in closed-cell polyurethane-epoxy rigid foam, but it is a monolithic block foam material, not a spherical filling unit. Chinese patent CN107805318A discloses a hollow sphere composite material for solid buoyancy, using expanded polystyrene (EPS) as the core and a shell layer formed by roller coating with thermosetting resin. This technology also suffers from interface problems between the EPS core and shell, and requires multiple coating processes, resulting in low production efficiency. Other existing polymer foamed bead technologies generally suffer from small particle size (<10mm), open surface, high water absorption, lack of a dense skin, and poor water pressure resistance, failing to meet the requirements for use in deep-sea high-pressure environments.
[0005] In summary, the existing polyurethane foaming technologies mentioned above mostly use ordinary polyether polyols, which have low primary hydroxyl content and insufficient reactivity. Furthermore, small molecule chain extenders react faster than polyether polyols, easily leading to problems such as uneven local crosslinking, unstable cell structure, and large fluctuations in mechanical properties. Although self-skinning polyurethane foam can form a dense skin, it is used for mold opening or simple molding of conventional shaped products, and does not involve high-pressure injection and gradient foaming control in spherical closed molds, nor does it involve the preparation of large-sized spherical products. Summary of the Invention
[0006] To overcome the shortcomings of the prior art, this invention provides a lightweight closed-cell bead for solid buoyancy materials, characterized by a controllable reaction process, uniform cross-linked network, no interfacial delamination, large size, high closed-cell rate, low water absorption, high pressure resistance, strong bonding with the matrix, and high production efficiency, as well as its preparation method and application.
[0007] The core solution of this invention is to use a highly active end-hydroxyl polyether polyol system, combined with bisphenol A and bisphenol F epoxy resin to form an interpenetrating network through synergistic reinforcement. Through a high-pressure injection molding gradient foaming process, stepwise orderly cross-linking is achieved by utilizing the difference in reactivity. This results in a one-time molding of an integrally formed spherical bead with an "integrated dense skin-uniform closed-cell core layer" structure. This fundamentally solves the core-shell interface problem of existing coated hollow spheres, the cost and breakage problem of hollow glass microspheres, and the water pressure resistance and water absorption rate problem of ordinary foamed beads.
[0008] To achieve the above objectives, the present invention adopts the following technical solution:
[0009] The first aspect of this invention is to provide a lightweight closed-cell bead for solid buoyancy materials, wherein the closed-cell bead is an integrally molded spherical structure of polyurethane-epoxy resin interpenetrating network foam, without core-shell interface delamination; comprising an integral dense skin layer on the surface and an internal closed-cell foamed core layer, wherein the skin layer and the core layer are continuously chemically bonded; wherein:
[0010] The thickness of the skin layer is 0.4~0.6mm, and it is a high cross-linking density polyurethane-epoxy resin interpenetrating network structure;
[0011] The core layer is a uniform closed-cell polyurethane-epoxy resin interpenetrating network foam structure with an average pore size of 80~200μm and a pore size variation coefficient ≤15%.
[0012] The closed-cell beads have a diameter of 20-100 mm and a density of 0.15-0.40 g / cm³. 3 The closed-cell rate is ≥96%, and the interfacial shear strength with the epoxy resin matrix is ≥8MPa when tested according to the method specified in this instruction manual.
[0013] Preferably, the closed-cell beads have a hydrostatic pressure of 11.5~20.8MPa, a water absorption rate of ≤1.0% under normal pressure for 24 hours, and a water absorption rate of ≤3.0% under 10MPa pressure for 1 hour.
[0014] Preferably, the relative mass fraction of epoxy resin in the skin layer is 30-50% higher than that in the core layer, and the epoxy resin forms a synchronous interpenetrating network with the polyurethane during the foaming process.
[0015] A second aspect of the present invention is to provide a method for preparing lightweight closed-cell beads for solid buoyancy materials as described in any of the preceding claims, comprising the following steps:
[0016] (1) Raw material preparation: Polyurethane foam component A and component B are prepared separately; component A includes, by weight: 45-55 parts of terminal primary hydroxyl polyether polyol, 12-22 parts of epoxy resin, 1.5-2.5 parts of silicone foam stabilizer, 0.8-1.5 parts of composite catalyst, 3-7 parts of composite foaming agent, and 2.5-4 parts of chain extender; component B is a modified polyisocyanate with an isocyanate index of 1.08-1.15;
[0017] (2) Mold pretreatment: Two precision-machined hemispherical molds are joined together to form a spherical mold cavity. The mold is preheated to 40~50°C. A release agent is sprayed on the inner surface of the mold cavity. A venting groove with a width of 0.15~0.25mm is set at the mold joint.
[0018] (3) High-pressure injection mixing: A polyurethane high-pressure injection molding machine is used. The temperature of component A is controlled at 22~28°C and the temperature of component B is controlled at 27~33°C. The two components are delivered to the high-pressure mixing head according to the metering ratio and mixed at high speed at 5500~7500rpm. The mixture is injected into the closed spherical mold cavity while mixing. The injection pressure is 12~18MPa, the injection time is 0.8~3.0s, and the material filling coefficient is controlled at 0.87~0.93.
[0019] (4) Gradient in-mold foaming: After injection, the mold is locked immediately and the material is cured at 45-55°C for 8-15 minutes in a gradient manner to form a dense skin layer on the surface and a closed-cell foam core layer inside. The specific formation mechanism is as follows: taking advantage of the fact that the reactivity of the terminal primary hydroxyl polyether polyol is higher than that of the small molecule chain extender, the highly active polyether first reacts with the isocyanate to form a prepolymer skeleton, and then gradually crosslinks with the chain extender. The reaction proceeds in an orderly manner step by step. The surface layer of the material in contact with the mold wall is rapidly gelled within 0.5-1.0 s to form a dense skin with high crosslinking density. After the skin is formed, the internal material is foamed at a uniform speed under adiabatic conditions to form a closed-cell core layer with uniform pore size.
[0020] (5) Post-curing treatment: Open the mold and take out the large beads. Cure them at 75~85°C for 2.5~3.5h to allow the resin system to react completely. Then cool naturally to room temperature to obtain the finished product.
[0021] Preferably, the primary hydroxyl-terminated polyether polyol in step (1) is one or more of the following: high-activity polyether polyol 3000E, polytetrahydrofuran diol PTMG-2000, and PTMG-1000, mixed in proportion, with a primary hydroxyl content ≥80%, an average molecular weight of 1000~3000, and an average functionality of 2~3.
[0022] Preferably, the epoxy resin in step (1) is a compound of bisphenol A type epoxy resin E-51 and bisphenol F epoxy resin 170 in a mass ratio of (2~3):1, with an average epoxy value of 0.45~0.55mol / 100g.
[0023] Preferably, the composite catalyst in step (1) is a mixture of triethylenediamine A33 and dibutyltin dilaurate T-12 in a mass ratio of (4~6):1 to achieve a matching of the gelation reaction rate and the foaming reaction rate;
[0024] The composite foaming agent is a mixture of deionized water and HCFC-141b at a mass ratio of 1:(5~7);
[0025] The chain extender is 1,4-butanediol.
[0026] Preferably, the modified polyisocyanate in step (1) is a compound of polymethylene polyphenyl polyisocyanate PM-200 and carbodiimide modified MDI-100HL in a mass ratio of (2.5~4.0):1, with an NCO mass fraction of 29~31%.
[0027] Preferably, the temperature field distribution of the gradient foaming in step (4) is as follows: the mold wall temperature is 45~55°C, the highest temperature at the center of the mold cavity does not exceed 120°C during the foaming process, the skin formation time is 0.5~1s, and the core layer foaming and curing time is 5~10min.
[0028] Preferably, the diameter of the hemispherical mold cavity in step (2) is 20~100mm, and the surface roughness Ra of the mold is ≤0.8 μm, to ensure that the surface of the large bead is smooth and round.
[0029] The third aspect of the present invention is to provide an application of lightweight closed-cell beads as described in any of the above claims in solid buoyancy materials for water depths of 1000-2000 meters, deep-sea riser buoyancy modules, underwater robot buoyancy systems, and marine buoys.
[0030] The present invention adopts the above technical solution and has the following technical effects compared with the prior art:
[0031] (1) Innovative reaction control and stepwise orderly crosslinking: This invention uses highly active terminal primary hydroxyl polyether polyol (primary hydroxyl content ≥80%), and utilizes the difference in reactivity between primary hydroxyl groups and small molecule chain extenders to achieve a stepwise reaction of "first forming the skeleton, then crosslinking". The crosslinking network is uniform and dense, the cell structure is uniform, and the pore size variation coefficient is ≤15%, which effectively solves the problems of uneven crosslinking and high internal stress in traditional polyurethane foaming.
[0032] (2) Synergistic reinforcement with epoxy resin: By compounding bisphenol A type epoxy resin E-51 with bisphenol F epoxy resin 170 at a ratio of (2~3):1, both the strength of the material and the viscosity and compatibility of the system are ensured. Bisphenol F epoxy resin 170 has a low viscosity, and its compounding with E-51 can effectively reduce the viscosity of the system, improve the cell structure, and at the same time improve the toughness and low-temperature resistance of the material. Compared with pure polyurethane foam, the interpenetrating network structure increases the compressive strength by more than 40% and significantly improves the hydrolysis resistance.
[0033] (3) Structural innovation, integrated interface-free structure: The large beads of this invention are an integrated integral molding structure of polyurethane-epoxy resin interpenetrating network foaming, with the skin and core layer continuously chemically bonded, and no core-shell interface. Compared with the EPS core + epoxy shell coating structure of CN105037789A, it completely solves the problem of core-shell delamination under high pressure; compared with hollow glass microspheres, there is no problem of glass-resin interface debonding.
[0034] (4) Performance innovation, high specific strength and low water absorption: The skin thickness of this invention is only 0.4~0.6mm, which is much thinner than the 0.5~2.5mm of coated hollow spheres. Under the same density, the effective buoyancy is increased by more than 20%; the closed-cell rate is ≥96%, the water absorption rate in 24 hours is ≤1.0%, and the water absorption rate under 10MPa high pressure is ≤3.0%, which is far superior to existing technology products.
[0035] (5) Process innovation, one-time high-pressure injection molding: The present invention adopts the high-pressure injection in-mold foaming process, and the single mold molding cycle is only 8~15min. The production efficiency is more than 10 times that of the traditional roller coating process (single ball production cycle ≥2h); the product has high dimensional accuracy and good consistency, and can produce large-size beads with a maximum diameter of 100mm, breaking through the size limit of 50mm of the existing technology.
[0036] (6) Interface innovation and strong bonding with the matrix: The surface of the large beads of the present invention is an active polyurethane-epoxy resin surface, which contains a large number of reactive hydroxyl and amino groups, and can form chemical bonds with the epoxy resin matrix. The interfacial shear strength is ≥8MPa, which is more than twice that of hollow glass microspheres and coated hollow spheres. Attached Figure Description
[0037] Figure 1This is a schematic cross-sectional view of the lightweight closed-cell beads of the present invention, showing the internal closed-cell foam core layer and the externally encapsulated integrated dense skin layer.
[0038] Figure 2 This is a schematic diagram of the in-mold gradient foaming molding mechanism of the present invention. Figure (a) shows the material injection stage; Figure (b) shows the rapid skin formation stage; and Figure (c) shows the foaming completion stage.
[0039] Figure 3 This is a scanning electron microscope image of the transition zone between the skin layer and the core layer in the lightweight closed-cell beads of the present invention.
[0040] Figure 4 This is a scanning electron microscope image of the pore morphology of the core layer of the lightweight closed-cell beads of the present invention.
[0041] Figure 5 These are photographs of lightweight closed-cell beads of different diameters from the present invention, fully demonstrating their smooth and round appearance.
[0042] Figure 6 This is a comparison chart of the hydrostatic pressure strength of the embodiments of the present invention and the comparative examples under similar densities. Detailed Implementation
[0043] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be described in further detail below with reference to the accompanying drawings and specific embodiments. The following detailed descriptions and embodiments are intended to explain the invention and are not intended to limit the scope of the invention in any way.
[0044] First, such as Figure 1 As shown, this invention provides a lightweight closed-cell bead for solid buoyancy materials. This lightweight closed-cell bead is an integrated, monolithic spherical structure formed by the integral foaming of a polyurethane-epoxy resin interpenetrating network, without a core-shell interface. It includes an integral, dense outer skin layer and an inner closed-cell foamed core layer. The skin layer and the core layer are continuously chemically bonded without a physical interface. The thickness of the skin layer is 0.4~0.6 mm, and it is a high-crosslinking-density polyurethane-epoxy resin interpenetrating network structure. The core layer is a uniform closed-cell polyurethane-epoxy resin interpenetrating network foamed structure with an average pore size of 80~200 μm and a pore size variation coefficient ≤15%. The diameter of the lightweight closed-cell bead is 20~100 mm, and the density is 0.15~0.40 g / cm³. 3 The closed-cell rate is ≥96%. When tested according to the method specified in this instruction manual, the interfacial shear strength with the epoxy resin matrix is ≥8 MPa, the hydrostatic pressure strength is 11.5~20.8 MPa, the water absorption rate at normal pressure for 24 hours is ≤1.0%, and the water absorption rate at 10 MPa pressure for 1 hour is ≤3.0%.
[0045] Secondly, such as Figure 2As shown, the preparation method of the above-mentioned lightweight closed-cell beads includes the following steps:
[0046] (1) Raw material preparation: Polyurethane foam component A and component B are prepared separately; component A includes, by weight: 45-55 parts of terminal primary hydroxyl polyether polyol, 12-22 parts of epoxy resin, 1.5-2.5 parts of silicone foam stabilizer, 0.8-1.5 parts of composite catalyst, 3-7 parts of composite foaming agent, and 2.5-4 parts of chain extender; component B is a modified polyisocyanate, with the isocyanate index controlled at 1.08-1.15;
[0047] (2) Mold pretreatment: Two precision CNC machined aluminum alloy hemispherical molds are joined together to form a spherical mold cavity. A high-pressure injection mixing head is set on the mold. The mold is preheated to 40~50℃. Semi-permanent mold release agent is sprayed on the inner surface of the mold cavity. A venting groove with a width of 0.15~0.25 mm is set at the mold joint to ensure that air is discharged smoothly and to avoid material flash.
[0048] (3) High-pressure injection mixing: A polyurethane high-pressure injection machine is used. The temperature of component A is controlled at 22~28℃ and the temperature of component B is controlled at 27~33℃. The two components are accurately delivered to the high-pressure injection mixing head according to the metering ratio. At a speed of 5500~7500 rpm, molecular-level mixing is achieved through high-speed collision and mechanical stirring to form a mixture. The mixture is injected into the closed spherical mold cavity while mixing. The injection pressure is 12~18MPa and the injection time is 0.8~3.0 s. The material filling coefficient is controlled to be 0.87~0.93.
[0049] (4) Gradient in-mold foaming: Immediately after injection, the mold is locked and cured at 45~55℃ for 8~15 min. Utilizing the characteristic that the reactivity of terminal primary hydroxyl polyether polyol is significantly higher than that of small molecule diol chain extenders, the primary hydroxyl groups of the highly active polyether preferentially react with isocyanate to first form a prepolymer skeleton with uniform molecular weight, and then undergo a stepwise crosslinking reaction with the chain extender. The entire reaction process proceeds in an orderly manner, resulting in a uniform and dense crosslinking network, effectively avoiding defects such as crosslinking point agglomeration, high internal stress, and uneven cell structure caused by the local rapid reaction of small molecule chain extenders. After the material is injected into the mold cavity, the surface material in contact with the high-temperature mold wall is at 0.5~1.0℃. Rapid gelation occurs within the membrane, where isocyanate reacts rapidly with polyether polyol and epoxy resin to form a dense skin with high cross-linking density. After the skin is formed, it functions as a sealed reaction vessel, where the internal materials react and foam at a uniform rate under the thermal protection of the skin, forming a closed-cell core layer with uniform pore size. Due to the reaction rate gradient, epoxy resin migrates and accumulates towards the high-temperature mold wall surface. The relative mass fraction of epoxy resin in the skin layer is 30-50% higher than that in the core layer. The addition of bisphenol F epoxy resin 170 effectively reduces the viscosity of the system, improves the compatibility between epoxy resin and polyurethane, and further enhances the strength, toughness, and barrier properties of the skin.
[0050] (5) Post-curing treatment: After opening the mold and taking out the large beads, post-curing at 75~85℃ for 2.5~3.5h allows the polyurethane and epoxy resin to react completely to form a stable interpenetrating network structure. After naturally cooling to room temperature, the finished product is obtained.
[0051] The primary hydroxyl-terminated polyether polyol mentioned in step (1) is one or more of the following: high-activity polyether polyol 3000E (polypropylene oxide-ethylene oxide triol, primary hydroxyl content ≥85%), polytetrahydrofuran diol PTMG-2000, and PTMG-1000, in a specific ratio. The average molecular weight is 1000~3000, and the average functionality is 2~3. The high primary hydroxyl content ensures that the reactivity of the polyether polyol is significantly higher than that of small molecule chain extenders, enabling the reaction to proceed in a stepwise and orderly manner.
[0052] The epoxy resin mentioned in step (1) is a compound of bisphenol A type epoxy resin E-51 and bisphenol F epoxy resin 170 at a mass ratio of (2~3):1, with an average epoxy value of 0.45~0.55 mol / 100g. Bisphenol F epoxy resin has low viscosity and good compatibility. When used in combination with E-51, it can effectively reduce the viscosity of the system, improve the cell structure, and at the same time improve the toughness and low-temperature resistance of the material. The hydroxyl groups in the epoxy resin can participate in the isocyanate reaction. The epoxy groups undergo ring-opening polymerization under the action of amine catalysts to form a synchronous interpenetrating network (SIN) with polyurethane, which significantly improves the compressive strength, hydrolysis resistance and dimensional stability of the material.
[0053] The composite catalyst mentioned in step (1) is a mixture of triethylenediamine A33 and dibutyltin dilaurate T-12 in a mass ratio of (4~6):1, which precisely adjusts the gelation and foaming reaction rates to ensure reaction balance and avoid bubble collapse or pore opening; the composite foaming agent is a mixture of deionized water and HCFC-141b in a mass ratio of 1:(5~7), and the product density is precisely controlled by adjusting the amount of foaming agent; the chain extender is 1,4-butanediol, which adjusts the hard segment content and improves the material strength.
[0054] The modified polyisocyanate mentioned in step (1) is a compound of polymethylene polyphenyl polyisocyanate PM-200 and carbodiimide modified MDI-100HL in a mass ratio of (2.5~4.0):1, with an NCO mass fraction of 29~31%. The addition of carbodiimide modified MDI can improve the hydrolysis resistance and toughness of the material.
[0055] The temperature field distribution for gradient foaming in step (4) is as follows: mold wall temperature 45~55℃, mold cavity center temperature not exceeding 120℃ during foaming, skin formation time 0.5~1.0s, and core layer foaming and curing time 5~10min. By precisely controlling the temperature field and reaction rate difference, the integrated continuous molding of the skin and core layer is achieved without any interface delamination.
[0056] The skin formation mechanism of this invention: The core innovation of this invention lies in utilizing the difference in reactivity of terminal primary hydroxyl polyethers and the gradient temperature field within the mold to achieve the controllable formation of an integrated skin. When the mixed material is injected into the high-temperature mold cavity, the material within 0.5 mm of the mold wall is instantly heated to 45~55℃. Under high catalyst concentration, the highly active primary hydroxyl groups preferentially react with isocyanate rapidly, completing gelation before the foaming agent generates bubbles, forming a non-porous dense layer. Simultaneously, due to the temperature gradient, the low-viscosity bisphenol F epoxy resin drives the epoxy resin to migrate and accumulate to the surface of the high-temperature mold wall, forming a higher crosslinking density in the skin layer. This process is completed within 1 second. The resulting dense skin not only has excellent mechanical strength and waterproof barrier properties, but also has a continuous chemical bond with the internal foamed core layer, without any physical interface, fundamentally different from the shells formed by post-coating, coating, and other processes in existing technologies.
[0057] I. Raw Material Sources and Specifications
[0058] The main raw materials used in the embodiments and comparative examples of this invention are shown in Table 1 below.
[0059] Table 1. Summary of main raw materials used in the embodiments and comparative examples of the present invention
[0060] Note: Unless otherwise specified above, all other raw materials and reagents are commercially available industrial-grade or analytical-grade products and can be obtained through commercial channels.
[0061] II. Testing Methods
[0062] Performance testing was conducted using the following methods:
[0063] (1) Density: Tested according to GB / T 6343-2009 "Determination of apparent density of foamed plastics and rubber". Take 3 large beads as a group, measure their mass and volume, and take the arithmetic mean.
[0064] (2) Closed cell ratio: Tested according to GB / T 10799-2008 "Determination of open and closed cell volume percentage of rigid foamed plastics" using the gas displacement method (AccuPyc II 1340 true density meter), each sample was tested 3 times and the average value was taken.
[0065] (3) Compressive strength: Tested according to GB / T 8813-2008 "Determination of compressive properties of rigid foamed plastics". The large beads were processed into cylindrical specimens with a diameter-to-height ratio of 1:1. The compression rate was 5 mm / min. The compressive stress at 10% strain was taken. Five specimens were tested in each group and the average value was taken.
[0066] (4) Hydrostatic pressure strength: Place a single large bead in a high-pressure container and pressurize it to the set pressure at a rate of 0.1 MPa / min. After holding the pressure for 1 hour, depressurize it at a rate of 0.5 MPa / min. After taking it out, observe whether the large bead breaks, collapses or undergoes obvious plastic deformation under visual inspection and magnification. Record the highest pressure at which no damage occurs in each group of 10 samples as the hydrostatic pressure strength value.
[0067] (5) Water absorption rate under normal pressure: Tested according to GB / T 8810-2005 "Determination of water absorption rate of rigid foam plastics". Immerse the large beads in distilled water at 23°C for 24 hours, take them out, wipe the surface moisture with filter paper, weigh them, calculate the percentage increase in mass, and take the average value of 5 beads in each group.
[0068] (6) High pressure water absorption rate: Place the large beads in a high pressure container, inject distilled water, pressurize to 10MPa and hold for 1 hour, release the pressure and take them out, use filter paper to absorb the surface moisture and weigh them, calculate the percentage increase in mass, and take the average value of 5 beads in each group.
[0069] (7) Skin thickness: The large bead is precisely cut along the diameter and the thickness of the dense, bubble-free area on the surface of the cross section is measured under an optical microscope (Nikon LV100ND). Ten measurement points are taken from the circumference of the cross section, and the arithmetic mean, maximum value and minimum value are taken.
[0070] (8) Average pore size and pore size variation coefficient: After the core layer sample of the large bead was subjected to liquid nitrogen brittle fracture and gold sputtering treatment, it was observed and photographed under a scanning electron microscope (Hitachi S-4800). The diameter of 200 bubbles (diameter of equal area circles) was randomly counted, and the arithmetic mean and standard deviation were calculated. The variation coefficient was calculated according to "standard deviation / average value × 100%".
[0071] (9) Interfacial shear strength: Place a single large bead in the center of a cylindrical mold, pour epoxy resin (E-51 / m-phenylenediamine = 100 / 25, mass ratio) to cover it, and process it into a standard sample after curing. Use a universal testing machine to push the large bead out of the resin matrix at a loading rate of 2 mm / min, record the maximum load, and calculate the interfacial shear strength according to the formula τ=F / (π·D·L) (τ—interfacial shear strength, MPa; F—maximum load when pushed out, N; D—diameter of the large bead, mm; L—embedding depth, mm). Take the average value of 5 beads in each group.
[0072] (10) Determination of epoxy resin content in the skin layer: Samples were scraped from the surface to the inside of the large beads radially (the surface layer (0-0.3 mm) is the skin layer, and the core layer (1.0-2.0 mm) is the core layer). Fourier transform infrared spectroscopy (FTIR, Thermo Nicolet 6700) in ATR mode was used for determination at 1508 cm⁻¹. -1 The absorption peak of the benzene ring skeleton vibration is at 1110 cm⁻¹ -1The relative content of epoxy resin is calculated by the ratio of the peak areas of the polyether COC absorption peaks.
[0073] III. Example Set
[0074] Example 1: Standard closed-cell beads with a diameter of 50mm
[0075] (1) Raw material preparation:
[0076] Component A is formulated in the following parts by weight: 40 parts of high-activity polyether polyol 3000E, 15 parts of polytetrahydrofuran diol PTMG-1000, 10 parts of E-51 epoxy resin, 5 parts of bisphenol F epoxy resin 170, 2 parts of foam stabilizer B8462, 1.0 parts of catalyst A33, 0.2 parts of catalyst T-12, 0.7 parts of deionized water, 4.5 parts of HCFC-141b, and 3 parts of 1,4-butanediol (BDO).
[0077] The specific preparation procedure is as follows: Weigh polyether 3000E and PTMG-1000 according to the specified ratio and add them to a stainless steel mixing vessel. Start stirring (500 rpm) and mix for 10 min. Add E-51 epoxy resin and bisphenol F epoxy resin 170 sequentially, and continue stirring for 15 min until uniformly mixed. Add foam stabilizer B8462 and stir for 10 min. Add composite catalyst A33 and T-12 and stir for 10 min. Finally, add deionized water, HCFC-141b composite foaming agent, and BDO chain extender, and increase the stirring speed to 2000 rpm for high-speed dispersion for 30 min. Transfer the prepared component A to a storage tank, turn on the vacuum degassing device, and degas for 15 min under a vacuum degree ≤ -0.095 MPa. Then, keep the component A storage tank at a constant temperature of 25°C for later use.
[0078] Component B was prepared according to the following ratio: 45 parts of polymethylene polyphenyl polyisocyanate PM-200 and 15 parts of carbodiimide-modified MDI MDI-100HL. The two isocyanates were added to a stainless steel mixing vessel according to the ratio and stirred at 300 rpm for 20 minutes under nitrogen protection until homogeneous. The NCO content was sampled and adjusted to the target value of 30.2%, with an isocyanate index of 1.10 (i.e., an NCO / OH molar ratio of 1.10). Component B was stored in a constant temperature of 30°C for later use.
[0079] (2) Mold pretreatment:
[0080] A precision CNC-machined aluminum alloy hemispherical mold with a cavity diameter of 50 mm and mirror-polished surface (Ra≤0.4 μm) was used. The upper and lower mold halves were mounted on the moving and fixed mold plates of a high-pressure injection molding machine, respectively. A semi-permanent silicone release agent was uniformly sprayed onto the inner surface of the mold cavity (spraying pressure 0.3 MPa, spray gun distance 200 mm, spray thickness approximately 5 μm). The mold was preheated to 45°C using a mold temperature controller and held at that temperature for 30 minutes to ensure uniform and stable temperature. After mold closing, the mold joint was inspected; the width of the venting groove was 0.20 mm, verified using a feeler gauge.
[0081] (3) High-pressure injection mixing:
[0082] Start the polyurethane high-pressure injection molding machine (Hennecke HK 300 model). Set the metering pumps for component A and component B to 100 parts and 60 parts respectively (mass ratio 100:60). Activate the material temperature control system to maintain the actual temperature of component A at 25°C and component B at 30°C. Set the high-pressure mixing head speed to 6500 rpm and the injection pressure to 15 MPa. Start the injection program. Components A and B in the high-pressure mixing head achieve molecular-level mixing through high-speed collision. The mixed material is injected into the closed spherical mold cavity through the injection nozzle. The injection time is 1.2 seconds. The actual injection volume is precisely controlled by the metering pumps, and the material filling factor is 0.90.
[0083] (4) Gradient in-mold foaming:
[0084] Immediately after injection, the mold is locked and pressure is maintained. The mold temperature controller is set to 50°C, and the material is cured at this temperature for 10 minutes. After the material is injected into the mold cavity, the surface material near the mold wall (45°C) rapidly gels within 0.5 seconds. Utilizing the significantly higher reactivity of terminal primary hydroxyl polyethers (primary hydroxyl content ≥85%) compared to small molecule 1,4-butanediol chain extenders, the primary hydroxyl groups of the highly reactive polyether preferentially react with isocyanates, forming a uniform prepolymer skeleton before bubble nucleation. Subsequently, the chain extender gradually participates in crosslinking, forming a uniform and dense crosslinked network. After the surface skin is formed, the internal material gradually increases in temperature under the thermal protection of the skin (the highest temperature at the center is approximately 110°C). The foaming agent vaporizes, causing the cells to grow uniformly and forming a closed-cell core layer. Throughout the foaming process, the internal pressure of the mold cavity is naturally balanced through the venting channels.
[0085] (5) Post-curing treatment:
[0086] After curing, the mold is opened, and the large beads are removed from the mold cavity with the assistance of compressed air. The large beads are placed in a forced-air constant-temperature oven and heated to 80°C at a heating rate of 2°C / min. After maintaining the temperature for 3 hours, the polyurethane and epoxy resin react completely to form a stable interpenetrating network structure. After post-curing, the oven power is turned off, and the beads are allowed to cool naturally to room temperature (cooling rate of approximately 1°C / min) to obtain the finished product.
[0087] The resulting large beads are white in appearance, with a smooth and round surface, free of burrs or flash. When cut along the diameter, a clear dense outer skin layer (0.5 mm thick) and a uniform closed-cell core layer are visible. There is a gradual transition between the skin layer and the core layer, with no visible interface delamination. Performance test results are shown in Table 2.
[0088] Example 2: High-strength closed-cell beads with a diameter of 30mm
[0089] (1) Raw material preparation:
[0090] Component A is formulated in the following parts by weight: 35 parts of high-activity polyether polyol 3000E, 12 parts of polytetrahydrofuran diol PTMG-2000, 15 parts of E-51 epoxy resin, 7 parts of bisphenol F epoxy resin 170, 2.5 parts of foam stabilizer B8462, 1.2 parts of catalyst A33, 0.25 parts of catalyst T-12, 0.5 parts of deionized water, 2.5 parts of HCFC-141b, and 3.5 parts of 1,4-butanediol (BDO).
[0091] The preparation method is the same as in Example 1. After the A group is prepared, it is stored at a constant temperature of 25°C.
[0092] Component B was prepared according to the following ratio: 52 parts of polymethylene polyphenyl polyisocyanate PM-200 and 13 parts of carbodiimide-modified MDI MDI-100HL. After thorough mixing, the isocyanate index was 1.15 and the NCO content was 30.8%. It was then stored at a constant temperature of 30°C.
[0093] (2) Mold pretreatment:
[0094] A precision aluminum alloy hemispherical mating mold with a diameter of 30 mm is used, and the surface roughness Ra ≤ 0.4 μm. After spraying the release agent, the mold is preheated to 50°C using a mold temperature controller and held at that temperature for 20 minutes to ensure uniform temperature. The width of the venting groove in the mold joint is 0.15 mm.
[0095] (3) High-pressure injection mixing:
[0096] The metering ratio of components A and B was set to 100:65, the material temperature of component A was 25°C, and the material temperature of component B was 30°C. The high-pressure mixing head speed was 7000 rpm, the injection pressure was 16 MPa, the injection time was 0.8 s, and the material filling coefficient was 0.92. The injection operation was the same as in Example 1.
[0097] (4) Gradient in-mold foaming:
[0098] After injection molding, the mold is locked, and the mold temperature controller is set to 55°C. The mold is then cured at this temperature for 8 minutes. The surface skin formation time is 0.5 seconds, the core layer foaming and curing time is approximately 6 minutes, and the highest temperature at the center of the mold cavity is approximately 118°C.
[0099] (5) Post-curing treatment:
[0100] After removing the large beads, heat them to 85°C in a forced-air oven at 2°C / min, maintain the temperature for 2.5 hours, and then allow them to cool naturally to room temperature to obtain the finished product.
[0101] The resulting large beads are white with a slight yellow tinge, smooth and round, with a density of 0.38 g / cm³. 3 Due to its high epoxy resin content and the use of PTMG-2000 (with a large molecular weight), the material has a high crosslinking density and high rigidity, with a compressive strength of 11.3 MPa and a hydrostatic strength of 16.8 MPa, making it a high-strength product.
[0102] Example 3: Lightweight closed-cell beads with a diameter of 80mm
[0103] (1) Raw material preparation:
[0104] Component A is formulated in the following parts by weight: 42 parts of high-activity polyether polyol 3000E, 15 parts of polytetrahydrofuran diol PTMG-1000, 8 parts of E-51 epoxy resin, 4 parts of bisphenol F epoxy resin 170, 1.5 parts of foam stabilizer B8462, 0.8 parts of catalyst A33, 0.15 parts of catalyst T-12, 1.0 part of deionized water, 6 parts of HCFC-141b, and 2.5 parts of 1,4-butanediol (BDO).
[0105] The preparation method is the same as in Example 1, and the product is stored at a constant temperature of 25°C.
[0106] Component B was prepared according to the following ratio: 38 parts of polymethylene polyphenyl polyisocyanate PM-200 and 12 parts of carbodiimide-modified MDI MDI-100HL. After thorough mixing, the isocyanate index was 1.08 and the NCO content was 29.8%. It was then stored at a constant temperature of 30°C.
[0107] (2) Mold pretreatment:
[0108] A precision aluminum alloy hemispherical mating mold with a diameter of 80 mm is used, and the surface roughness Ra ≤ 0.8 μm. After spraying the release agent, the mold is preheated to 40°C using a mold temperature controller and held at that temperature for 40 min to ensure uniform temperature. The width of the venting groove in the mold joint is 0.25 mm.
[0109] (3) High-pressure injection mixing:
[0110] The metering ratio of components A and B is set to 100:50, the material temperature of component A is 25°C, and the material temperature of component B is 28°C. The high-pressure mixing head speed is 5500 rpm, the injection pressure is 12 MPa, the injection time is 2.0s, and the material filling coefficient is 0.88.
[0111] (4) Gradient in-mold foaming:
[0112] After injection, the mold is locked, and the mold temperature controller is set to 45°C. The material is cured at this temperature for 12 minutes. Due to the large diameter of the large beads (80 mm), the internal material stores a lot of heat. The highest temperature in the center of the mold cavity is about 120°C. The core layer foaming and curing time is about 10 minutes, and the surface skin formation time is 0.8 seconds.
[0113] (5) Post-curing treatment:
[0114] After removing the large beads, heat them to 75°C in a forced-air oven at 1.5°C / min, maintain the temperature for 3.5 hours, and then allow them to cool naturally to room temperature to obtain the finished product.
[0115] The resulting large beads are white in appearance, with a smooth and round surface, approximately 80 mm in diameter, and a density of only 0.18 g / cm³. 3 Due to the large amount of foaming agent used (7 parts total of water / HCFC-141b composite foaming agent), the material has high porosity and low density, making it a lightweight product suitable for buoyancy modules in shallow to medium waters where weight is a critical factor.
[0116] Example 4: Closed-cell beads with a diameter of 20 mm for ultra-deep water
[0117] (1) Raw material preparation:
[0118] Component A is formulated in the following parts by weight: 25 parts of polytetrahydrofurandiol PTMG-1000, 20 parts of polytetrahydrofurandiol PTMG-2000, 14 parts of E-51 epoxy resin, 6 parts of bisphenol F epoxy resin 170, 2.2 parts of foam stabilizer B8462, 1.3 parts of catalyst A33, 0.2 parts of catalyst T-12, 0.4 parts of deionized water, 2 parts of HCFC-141b, and 4 parts of 1,4-butanediol (BDO).
[0119] The preparation method is the same as in Example 1, and the product is stored at a constant temperature of 25°C.
[0120] Component B: Only 55 parts of polymethylene polyphenyl polyisocyanate PM-200 (without MDI-100HL) were used, with an isocyanate index of 1.12 and an NCO content of 31.5%, and stored at a constant temperature of 30°C.
[0121] (2) Mold pretreatment:
[0122] A precision aluminum alloy hemispherical mating mold with a diameter of 20mm is used, and the surface roughness Ra ≤ 0.4μm. After spraying the release agent, the mold is preheated to 50°C using a mold temperature controller and held at that temperature for 15 minutes to ensure uniform temperature. The width of the venting groove in the mold joint is 0.15mm.
[0123] (3) High-pressure injection mixing:
[0124] The metering ratio of components A and B is set to 100:55, the material temperature of component A is 25°C, and the material temperature of component B is 30°C. The high-pressure mixing head speed is 7500 rpm, the injection pressure is 18 MPa, the injection time is 0.8 s, and the material filling coefficient is 0.93.
[0125] (4) Gradient in-mold foaming:
[0126] After injection, the mold is locked, and the mold temperature controller is set to 55°C for curing for 8 minutes. The small-diameter mold cavity has high heat transfer efficiency, the surface skin formation time is only 0.4 seconds, and the highest temperature at the center of the mold cavity is about 115°C.
[0127] (5) Post-curing treatment:
[0128] After removing the large beads, heat them to 80°C in a forced-air oven at 2.5°C / min, maintain the temperature for 3 hours, and then let them cool naturally to room temperature to obtain the finished product.
[0129] The resulting large beads are light yellow in color, smooth and round, approximately 20 mm in diameter, and have a density of 0.40 g / cm³. 3 Due to the highest amount of chain extender BDO (4 parts) and the lowest amount of foaming agent (2.4 parts in total), the material has high crosslinking density and low porosity, with a compressive strength of 16.5 MPa, hydrostatic strength of 20.8 MPa, and interfacial shear strength of 11.0 MPa, making it a product for ultra-deep water and high-pressure environments.
[0130] Example 5: 100 mm diameter ultra-large closed-cell bead
[0131] (1) Raw material preparation:
[0132] Component A is formulated in the following parts by weight: 40 parts of high-activity polyether polyol 3000E, 18 parts of polytetrahydrofuran diol PTMG-2000, 10 parts of E-51 epoxy resin, 5 parts of bisphenol F epoxy resin 170, 1.8 parts of foam stabilizer B8462, 0.7 parts of catalyst A33, 0.12 parts of catalyst T-12, 1.1 parts of deionized water, 6.5 parts of HCFC-141b, and 2.8 parts of 1,4-butanediol (BDO).
[0133] The preparation method is the same as in Example 1, and the product is stored at a constant temperature of 25°C.
[0134] Component B was prepared according to the following ratio: 36 parts of polymethylene polyphenyl polyisocyanate PM-200 and 9 parts of carbodiimide-modified MDI MDI-100HL. After thorough mixing, the isocyanate index was 1.08 and the NCO content was 29.5%. It was then stored at a constant temperature of 28°C.
[0135] (2) Mold pretreatment:
[0136] A precision aluminum alloy hemispherical mating mold with a diameter of 100 mm is used, and the surface roughness Ra ≤ 0.8 μm. After spraying the release agent, the mold is preheated to 40°C using a mold temperature controller and held at that temperature for 50 minutes to ensure uniform temperature. The width of the venting groove in the mold joint is 0.25 mm.
[0137] (3) High-pressure injection mixing:
[0138] The metering ratio of components A and B is set to 100:45, the injection pressure is 12MPa, the high-pressure mixing head speed is 6000rpm, the injection time is 3.0s, and the material filling coefficient is 0.87.
[0139] (4) Gradient in-mold foaming:
[0140] After injection molding, the mold is locked, and the mold temperature controller is set to 45°C. The mold is then cured at this temperature for 15 minutes. The large-diameter (100mm) mold cavity exhibits a significant heat storage effect in the center, with a maximum temperature of approximately 120°C. The surface skin formation time is 1.0s, and the core layer foaming and curing time is approximately 12 minutes.
[0141] (5) Post-curing treatment:
[0142] After removing the large beads, heat them to 75°C in a forced-air oven at 1°C / min, maintain the temperature for 3.5 hours, and then allow them to cool naturally to room temperature to obtain the finished product.
[0143] The resulting large beads are white in appearance, with a smooth and round surface, approximately 100 mm in diameter, and a density of 0.15 g / cm³. 3 This product is currently the largest polymer lightweight closed-cell spherical filler unit, suitable for integrated filling of large buoyancy modules.
[0144] IV. Comparative Example Group
[0145] Comparative Example 1: Ordinary secondary hydroxyl polyether (no stepwise reaction effect)
[0146] The only difference between this comparative example and Example 1 is that the primary hydroxyl polyether 3000E is replaced with ordinary secondary hydroxyl polyether MN-500 (primary hydroxyl content <10%). All other components, ratios and process parameters are exactly the same as in Example 1.
[0147] The specific formulation of component A is as follows: 40 parts of polyether MN-500, 15 parts of PTMG-1000, 10 parts of E-51 epoxy resin, 5 parts of bisphenol F epoxy resin 170, 2 parts of B8462, 1.0 part of A33, 0.2 parts of T-12, 0.7 parts of deionized water, 4.5 parts of HCFC-141b, and 3 parts of BDO.
[0148] The preparation process is exactly the same as in Example 1.
[0149] Results Analysis: Because MN-500 is a secondary hydroxyl polyether (primary hydroxyl content <10%), its reactivity is lower than that of 1,4-butanediol chain extender, making it impossible to achieve the stepwise ordered reaction of "first forming the skeleton, then crosslinking". The small molecule BDO preferentially reacts with isocyanate, leading to premature formation of local crosslinking points, concentrated exothermic reactions, and disordered cell nucleation and growth processes. Although the resulting beads are spherical in appearance, their surface gloss is poor, and upon dissection, local hard spots and significant differences in cell size are visible. The pore size variation coefficient reaches 24% (only 10% in Example 1), the closed-cell rate is only 90%, and the hydrostatic strength is 9.1 MPa, a decrease of 34% compared to Example 1, demonstrating that the stepwise reaction mechanism of the terminal primary hydroxyl polyether is key to achieving the excellent performance of the material.
[0150] Comparative Example 2: Bisphenol F-free epoxy resin
[0151] The only difference between this comparative example and Example 1 is that bisphenol F epoxy resin 170 is not added, and the amount of E-51 epoxy resin is increased to 15 parts to keep the total amount of epoxy resin added unchanged (15 parts). All other components, proportions, and process parameters are exactly the same as in Example 1.
[0152] The specific formulation of component A is as follows: 40 parts of polyether 3000E, 15 parts of PTMG-1000, 15 parts of E-51 epoxy resin (BPS-free F170), 2 parts of B8462, 1.0 part of A33, 0.2 parts of T-12, 0.7 parts of deionized water, 4.5 parts of HCFC-141b, and 3 parts of BDO.
[0153] The preparation process is the same as in Example 1.
[0154] Results Analysis: Without the addition of bisphenol F epoxy resin 170, the system viscosity was high (approximately 8500 mPa·s at room temperature, compared to approximately 5200 mPa·s in Example 1), resulting in decreased mixing uniformity and uneven cell nucleation. The compatibility between the epoxy resin and polyurethane deteriorated, leading to insufficient interpenetrating network formation. The resulting large beads had a acceptable appearance, with a closed-cell rate of 95% and a compressive strength of 8.3 MPa, not significantly different from Example 1 (8.5 MPa). However, the coefficient of variation for pore size increased to 16%, and the high-pressure water absorption rate rose to 3.8% (compared to only 2.1% in Example 1). This indicates that the low viscosity and good compatibility of bisphenol F epoxy resin play an important role in improving the cell structure and enhancing the density of closed cells.
[0155] Comparative Example 3: Skin too thick (mold temperature too high)
[0156] The only difference between this comparative example and Example 1 is that the mold preheating temperature is increased from 45°C to 70°C and the curing temperature is increased from 50°C to 70°C. All other components, proportions, and process parameters are exactly the same as in Example 1.
[0157] Results Analysis: Due to the excessively high mold temperature (70°C), the surface reaction rate was too rapid after material injection, with gelation completed within 0.2 seconds. The skin formed prematurely and was excessively thick (up to 1.7 mm), resulting in a large amount of epoxy resin being "frozen" in the skin layer. This led to a relative scarcity of resin in the core layer, resulting in uneven cell structure and eccentric depressions in the large beads (skin thickness 2.1 mm on the upper mold side and only 1.3 mm on the lower mold side). Although the closed-cell rate still reached 96%, the density increased to 0.32 g / cm³. 3 Furthermore, due to the excessive thickness of the skin, the density distribution along the thickness direction of the large beads was severely uneven, and the hydrostatic pressure strength actually decreased to 12.8 MPa (lower than 13.8 MPa in Example 1), proving that 0.4~0.6 mm is the optimal range for skin thickness. This comparative example also shows that the mold temperature plays a key role in controlling the skin thickness, and exceeding the preferred temperature range will lead to the deterioration of product performance.
[0158] Comparative Example 4: Open-cell structure (insufficient foam stabilizer and catalyst)
[0159] The difference between this comparative example and Example 1 is that the amount of foam stabilizer B8462 is reduced from 2 parts to 0.5 parts, and T-12 catalyst is not added (i.e., the catalyst is only 1.0 part of A33, and there is no T-12). All other components, proportions and process parameters are the same as in Example 1.
[0160] The specific formulation of component A is as follows: 40 parts of polyether 3000E, 15 parts of PTMG-1000, 10 parts of E-51 epoxy resin, 5 parts of bisphenol F170, 0.5 parts of B8462, 1.0 part of A33, 0.7 parts of deionized water, 4.5 parts of HCFC-141b, and 3 parts of BDO (excluding T-12).
[0161] Results Analysis: Insufficient B8462 dosage led to the failure of foam surface tension regulation, resulting in severe cell merging and rupture. Without the T-12 catalyst, the gel reaction rate was too low, and the foam strength was insufficient to support the cell walls, causing numerous bubbles to rupture and connect during foaming. The resulting large beads had a rough surface covered with pinhole-like openings, and the internal cell structure was clearly interconnected upon dissection. The closed-cell rate was only 64%, the hydrostatic pressure strength was only 10.7 MPa, and the 24-hour water absorption rate was as high as 14.2%, completely failing to meet the requirements for deep-sea buoyancy materials. This comparative example demonstrates the crucial role of foam stabilizers and the composite catalytic system in achieving a high closed-cell rate.
[0162] Comparative Example 5: Coated hollow spheres prepared according to CN105037789A (Prior Art)
[0163] Comparative samples were prepared according to the method in Example 1 of CN105037789A:
[0164] (1) EPS core preparation: EPS foam beads with a diameter of about 45 mm (density about 0.03 g / cm³) were prepared using a steam foaming process. 3 The beads are treated with surface corona to enhance coating adhesion.
[0165] (2) Preparation of resin coating solution: E-51 epoxy resin and TETA curing agent are mixed evenly at a mass ratio of 5:1 and vacuum degassed for 15 minutes.
[0166] (3) Roller coating: Place the EPS core in a roller at a 15° angle, maintain the roller temperature at 35°C and the rotation speed at 15 rpm. Use a spray gun to spray the resin mixture onto the tumbling EPS surface, with each spray amount being approximately 8% of the core mass. After spraying, keep tumbling for 1 minute to allow the resin to spread evenly. Immediately spray short-cut glass fibers (fiber length 3mm, addition amount 12% of the resin mass), and continue tumbling for 5 minutes to allow the fibers to fully impregnate and embed into the resin layer.
[0167] (4) Curing: Raise the temperature of the roller to 60°C and cure for 45 minutes to solidify the resin gel.
[0168] (5) Repeat coating: Repeat steps (3) and (4) a total of 8 times until the ball diameter reaches about 50 mm.
[0169] (6) Final curing: The coated balls are cured at 80°C for 4 hours and then naturally cooled to obtain the final product.
[0170] The resulting coated hollow spheres are pale yellow in appearance, have a fibrous texture on the surface, and a density of approximately 0.25 g / cm³. 3 The shell is about 1.2mm thick.
[0171] Results Analysis: This comparative product exhibits a typical core-shell structure of "EPS core + epoxy resin / fiber shell," with the shell and core physically interlocked, showing significant structural discontinuity at the interface. It is similar to Example 1 (with the same density of 0.25 g / cm³). 3 Compared to the previous method, the shell thickness (1.2 mm) is 2.4 times that of the skin (0.5 mm) of this invention, the hydrostatic pressure strength is only 12.0 MPa (compared to 13.8 MPa of this invention), the water absorption rate under 10 MPa pressure is as high as 13.1% (compared to only 2.1% of this invention), and the interfacial shear strength is only 3.7 MPa (compared to 9.4 MPa of this invention). More importantly, after the 10 MPa pressure test, some coated balls showed local bulging and delamination of the outer shell, indicating that the core-shell interface separated under high pressure. This comparative example fully demonstrates that the integrated, integrally molded, interface-free structure of this invention has far superior comprehensive advantages in terms of water pressure resistance, water absorption resistance, and interfacial bonding compared to the core-shell coated structure of the prior art.
[0172] V. Performance Testing
[0173] Using the performance testing methods described in Part II above, various performance tests were conducted on the embodiment group and the comparative example group of the present invention. Table 2 shows a summary comparison of the key performance data of Embodiment 1 and Comparative Examples 1-5. Figure 3 shows a summary table of the performance test results of Embodiments 1-5.
[0174] Table 2 Summary of Performance Test Results for Example 1 and Comparative Example
[0175] Table 3 Summary of Performance Test Results for Examples 1-5
[0176] As can be seen from the test results in Tables 2 and 3, the closed-cell beads prepared in Examples 1 to 5 of this invention have excellent comprehensive performance, with a closed-cell rate of ≥96%, uniform pore size (coefficient of variation ≤13%), a hydrostatic pressure strength of up to 20.8MPa, a high-pressure water absorption rate of ≤2.7%, and an interfacial shear strength of ≥8.3MPa. All of these properties are significantly better than those of the comparative examples.
[0177] Comparative Example 1 (ordinary secondary hydroxyl polyether) could not achieve stepwise ordered crosslinking, with a pore size variation coefficient of 24%, a closed-cell rate of 90%, and a hydrostatic strength reduction of 34%, proving that the stepwise reaction mechanism of the terminal primary hydroxyl polyether is one of the core technical elements of this invention.
[0178] Comparative Example 2 (without bisphenol F epoxy resin) showed decreased cell uniformity and increased high-pressure water absorption rate, proving that the synergistic effect of bisphenol A and bisphenol F epoxy resin is irreplaceable.
[0179] Comparative Example 3 (skin thickness 1.7mm) showed increased density, product eccentricity, and decreased hydrostatic strength, proving that 0.4~0.6mm is the optimal process window for skin thickness.
[0180] The performance of Comparative Example 4 (open-cell structure) deteriorated sharply, demonstrating the decisive role of foam stabilizer and composite catalytic system in achieving high closed-cell ratio.
[0181] Comparative Example 5 (CN105037789A coated hollow sphere) has the risk of core-shell interface delamination. Its shell thickness is 2.4 times that of the present invention, but its hydrostatic strength is only 57.7% of that of the present invention, its high-pressure water absorption rate is 6.2 times that of the present invention, and its interfacial shear strength is only 39% of that of the present invention. Its overall performance is far lower than that of the product of the present invention.
[0182] The specific embodiments of the present invention have been described in detail above, but they are merely examples, and the present invention is not limited to the specific embodiments described above. For those skilled in the art, any equivalent modifications and substitutions to the present invention are also within the scope of the present invention. Therefore, all equivalent transformations and modifications made without departing from the spirit and scope of the present invention should be covered within the scope of the present invention.
Claims
1. A lightweight closed-cell bead for solid buoyancy materials, characterized in that, The closed-cell beads are integrally molded spherical structures formed by polyurethane-epoxy resin interpenetrating network foaming, without core-shell interface delamination. It includes an integrated dense skin layer on the surface and an internal closed-cell foam core layer, with the skin layer and core layer being continuously chemically bonded; wherein: The thickness of the skin layer is 0.4~0.6 mm, and it is a high cross-linking density polyurethane-epoxy resin interpenetrating network structure. The core layer is a uniform closed-cell polyurethane-epoxy resin interpenetrating network foam structure with an average pore size of 80~200μm and a pore size variation coefficient ≤15%. The closed-cell beads have a diameter of 20-100 mm and a density of 0.15-0.40 g / cm³. 3 The closed-cell ratio is ≥96%, and the interfacial shear strength with the epoxy resin matrix is ≥8 MPa.
2. The lightweight closed-cell beads for solid buoyancy materials according to claim 1, characterized in that, The closed-cell beads have a hydrostatic strength of 11.5~20.8 MPa, a water absorption rate of ≤1.0% under normal pressure for 24 h, and a water absorption rate of ≤3.0% under 10 MPa pressure for 1 h.
3. The lightweight closed-cell beads for solid buoyancy materials according to claim 1, characterized in that, The relative mass fraction of epoxy resin in the skin layer is 30-50% higher than that in the core layer.
4. A method for preparing lightweight closed-cell beads for solid buoyancy materials as described in any one of claims 1 to 3, characterized in that, Includes the following steps: (1) Raw material preparation: Polyurethane foam component A and component B are prepared separately; component A includes, by weight: 45-55 parts of terminal primary hydroxyl polyether polyol, 12-22 parts of epoxy resin, 1.5-2.5 parts of silicone foam stabilizer, 0.8-1.5 parts of composite catalyst, 3-7 parts of composite foaming agent, and 2.5-4 parts of chain extender; component B is a modified polyisocyanate with an isocyanate index of 1.08-1.15; (2) Mold pretreatment: Two precision-machined hemispherical molds are joined together to form a spherical mold cavity. The mold is preheated to 40~50°C. The inner surface of the mold cavity is sprayed with release agent. A 0.15~0.25 mm wide venting groove is set at the mold joint. (3) High-pressure injection mixing: A polyurethane high-pressure injection molding machine is used. The temperature of component A is controlled at 22~28°C and the temperature of component B is controlled at 27~33°C. The two components are delivered to the high-pressure mixing head according to the metering ratio and mixed at high speed at 5500~7500 rpm. The mixture is injected into the closed spherical mold cavity while mixing. The injection pressure is 12~18 MPa, the injection time is 0.8~3.0 s, and the material filling coefficient is controlled at 0.87~0.
93. (4) Gradient in-mold foaming: Immediately after injection, the mold is locked and the material is cured at 45~55°C for 8~15 min in a gradient manner to form a dense skin layer on the surface and a closed-cell foam core layer inside the material. (5) Post-curing treatment: After opening the mold and taking out the large beads, post-curing at 75~85°C for 2.5~3.5 h to allow the resin system to react completely, and then naturally cooling to room temperature to obtain the finished product.
5. The preparation method according to claim 4, characterized in that, The primary hydroxyl-terminated polyether polyol mentioned in step (1) is one or more of the following: high-activity polyether polyol 3000E, polytetrahydrofuran diol PTMG-2000, and PTMG-1000, compounded in proportion, with a primary hydroxyl content ≥80%, an average molecular weight of 1000~3000, and an average functionality of 2~3.
6. The preparation method according to claim 4, characterized in that, The epoxy resin mentioned in step (1) is a compound of bisphenol A type epoxy resin E-51 and bisphenol F epoxy resin 170 in a mass ratio of (2~3):1, with an average epoxy value of 0.45~0.55 mol / 100g.
7. The preparation method according to claim 4, characterized in that, The composite catalyst mentioned in step (1) is a mixture of triethylenediamine A33 and dibutyltin dilaurate T-12 in a mass ratio of (4~6):1; The composite foaming agent is a mixture of deionized water and HCFC-141b at a mass ratio of 1:(5~7); The chain extender is 1,4-butanediol.
8. The preparation method according to claim 4, characterized in that, The modified polyisocyanate mentioned in step (1) is a compound of polymethylene polyphenyl polyisocyanate PM-200 and carbodiimide modified MDI-100HL in a mass ratio of (2.5~4.0):1, with an NCO mass fraction of 29~31%.
9. The preparation method according to claim 4, characterized in that, The temperature field distribution of the gradient foaming in step (4) is as follows: the mold wall temperature is 45~55°C, the highest temperature in the center of the mold cavity does not exceed 120°C during the foaming process, the skin formation time is 0.5~1.0 s, and the core layer foaming and curing time is 5~10 min.
10. The application of a lightweight closed-cell bead as described in any one of claims 1 to 3 in solid buoyancy materials for water depths of 1000 to 2000 meters, deep-sea riser buoyancy modules, underwater robot buoyancy systems, and marine buoys.
Citation Information
Patent Citations
Fiber-reinforced resin composite material hollow ball and preparation method thereof
CN105037789A
Method for preparing composite hollow large ball for solid buoyancy materials and hollow large ball
CN107805318A
Buoyancy material with micro bubble and cell composite structure
CN1827691A